Revisiting the Identification and cDNA Cloning of T Cell-Replacing Factor/Interleukin-5 - Takatsu, Kiyoshi (Frontiers in Immunology, 2014)
This is a perspective based on the paper "Cloning of complementary DNA encoding T cell replacing factor and identity with B cell growth factor II", by Kinashi T, Harada N, Severinson E, Tanabe T, Sideras P, Konishi M, Azuma C, Tominaga A, Bergstedt-Lindqvist S, Takahashi M, Matsuda F, Yaoita Y, Takatsu K, and Honjo, T. Nature (1986) 32(6092): 70-3. We have been interested in understanding the molecular basis of T-B cell cooperation for antibody formation. Although many investigators had described a number of different soluble factors that appeared to have biological relevance to T-B cell interactions, molecular basis of such active substances remained unknown for a long period of time. In this perspective, I will briefly summarize the history of the initial discovery of T cell-replacing factor/B cell growth factor II that appeared to be involved in B-cell growth and differentiation, and outline the discovery and characterization of interleukin-5. Studies of interleukin-5 have provided strong evidence that a single cytokine exerts a variety of activities on diverse target cells.